2013
DOI: 10.1016/j.jsbmb.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Health characteristics and outcomes of two randomized vitamin D supplementation trials during pregnancy: A combined analysis

Abstract: Objective-To assess the safety and health effects of vitamin D supplementation during pregnancy.Methods and Design-Datasets from two randomized clinical trials were first analyzed separately then combined for this analysis using a common data dictionary. In the NICHD trial, women were randomized to 400, 2000, or 4000 IU vitamin D 3 /day, stratified by race. In the Thrasher Research Fund trial, participants were randomized to 2000 or 4000 IU vitamin D 3 /day. Study drugs were from the same manufacturing lot for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 26 publications
5
99
0
4
Order By: Relevance
“…Randomized controlled trials of vitamin D supplementation during pregnancy have clarified issues related to optimal dosing and safety (Wagner et al, 2013b, Wagner et al, 2013a but larger trials will be needed in order to focus on the range of adverse health outcomes associated with gestational vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials of vitamin D supplementation during pregnancy have clarified issues related to optimal dosing and safety (Wagner et al, 2013b, Wagner et al, 2013a but larger trials will be needed in order to focus on the range of adverse health outcomes associated with gestational vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Hollis and Wagner have subsequently carried out several post-hoc analyses of these two trials, including analyses in which selective data from both studies were pooled, out of which some borderline significant results have been obtained (399,401,963,964,967). However, these analyses suffer from lack of adjustment for multiple comparisons, arbitrary grouping of outcomes, and exclusion of some ethnicities from the analysis.…”
Section: Yu Etmentioning
confidence: 99%
“…6,7 Therefore, it was suggested that higher vitamin D supplementation might be required for prevention of hypovitaminosis D and achievement of normal circulating 25-OHD levels (40 to 60 ng ml -1 ) during pregnancy, which would also decrease the incidence of co-morbidities of pregnancy. 8,9 A more recent study showed that lower maternal 25-OHD levels were associated with increased risk of dental caries in infants. 10 All these data suggest the role of appropriate vitamin D supplementation that leads to higher maternal 25-OHD levels during pregnancy which would subsequently have beneficial effects in prevention of both maternal and neonatal morbidities.…”
Section: Introductionmentioning
confidence: 99%